Taxes Harmonization Features in the European Union Countries - Safonova, Margarita F.; Reznichenko, Dmitry S.; Melnichuk, Marina V.; Karaev, Alan K.; Litvinova, Svetlana F. (International Journal of Economics and Financial Issues, 2016)
Today the most developed integration association is the European Union, which main predecessor is the European Economic Community that was created in 1957. The challenge on the today’s agenda in the EU is the formation and strengthening of the economic, monetary and political union of the countries - members. The integration within the EU affects almost all relationship parties of the states - the EU members - politics, economics, social and cultural spheres. To indicate this process the term “tax harmonization” is used in the EU. The driving force and the motivation incentive of the taxation harmonization in the Member States of the European Union are the processes of the deepening of the international economic integration. At the same time, the tax systems rapprochement of the states involved in the integration association has the opposite stimulating effect on the further development of the integration processes in other areas. The research relevance is caused by the importance and special role of tax harmonization in the framework of the European economic integration deepening, the development of the EU united internal market, the economic and currency union formation in the EU. The study objectives is the determination of the tax harmonization and justification of its need for the integration association at the mature stages of its development, the identification and analysis of the factors affecting the pro- process of tax harmonization in the European Union countries. Keywords: economy, taxes, tax harmonization, the tax system regulation JEL Classifications: F33, G18, M48